The Effect of Adding Petrofish Probiotics to Fish Feed on the Growth Rate and Survival of Tilapia (Oreochromis Niloticus) UPTD Benih Ikan Dukupuntang Kabupaten Cirebon - Nabila, Ainin Nabila; Hikmawan, Sindi; Ekawati, Nurul; Novianti, Teni; Astuti, Lusia Cipto; Kusumah, Billi Rifa (Jurnal Tropika Bahari, 2023)
Tilapia (Oreochromis nilotius) is one of the freshwater consumption fish commodities. Tilapia has the ability to survive and adapt to any environmental conditions so that it is easy to breed, although in extreme conditions tilapia can survive well compared to other fish. In tilapia farming there are several obstacles, one of which is the presence of diseases caused by bacteria. Probiotics are one alternative to the addition of supplements to the feed of farmed fish. Therefore, this study aims to determine the effect of Petrofish probiotics on the growth and survival of tilapia. The method used in this study used an experimental method with a Complete Random Design (RAL) with 4 treatments and 3 repeats with treatment 1: commercial feed without probiotics, Treatment 2: commercial feed given additional 5 ml petrofish probiotics, Treatment 3: commercial feed given additional 10 ml petrofish probiotics, Treatment 4: commercial feed given additional 15 ml petrofish probiotics. Statistical analysis used SPSS 22 and the results were calculated by Analysis of Variance (ANOVA) and continued Duncan Test. Then to find out what percentage of the effect of feeding on tilapia growth rate is calculated using Multiple Linear Regression Test. The results showed that treatment 3 produced the best growth rate compared to other treatments, with a value of 871.5 grams and a tilapia survival rate of 80%. In addition, the addition of petrofish probiotics has a positive influence on the growth rate and survival of tilapia by 79%. Keywords : Petrofish Probiotics; Growth Rate; Survival.